Dessins D’Enfants on Reducible Surfaces - Ya. Amburg, Natalia; M. Kreines, Elena; B. Shabat, George (Sarajevo Journal of Mathematics, 2024)
In this paper we introduce dessins d'enfants on unions of surfaces, possibly glued. We show why they are natural, discuss their relations with Belyi pairs on reducible curves and provide some examples. In particular, we provide an example of a Fried pair which degenerates to a dessin on a reducible and singular curve.